PENGARUH MEDIA SOSIAL TERHADAP RELIGIUSITAS PRAJURIT TNI AD KODIM 1403/PALOPO - Windiyani Windiyani; Syahruddin Syahruddin; Adilah Mahmud (An-Nida : Jurnal Komunikasi Islam, 2024)
This thesis discusses the influence of social media on the religiosity of Indonesian Army Soldiers of Kodim 1403/Palopo. The aims are: 1) to find out how much influence social media has on the religiosity of Indonesian Army Soldiers of Kodim 1403/Palopo; 2) to find out the impact of social media on the religiosity of Indonesian Army Soldiers of Kodim 1403/Palopo; and 3) to analyze the understanding of Indonesian Army Soldiers of Kodim 1403/Palopo towards religiosity. The type of research used was field research with the Mixed Method method, the population was 659 Indonesian Army Soldiers of Kodim 1403/Palopo with a simple random sampling technique of 68 Soldiers. Data collection techniques were carried out by means of observation, questionnaires, interviews and documentation. The data was then analyzed using descriptive statistical analysis, simple regression analysis, and T-test using SPSS for Windows Version 20. The data was then analyzed using a qualitative approach through three steps, namely: data reduction, presentation of research data and drawing conclusions. The results of the study: 1) There is a positive and significant influence between social media and the religiosity of TNI AD Kodim 1403/Palopo soldiers by 54%, so H0 was rejected and H1 was accepted; 2) The impact of social media on the religiosity of TNI AD Kodim 1403/Palopo soldiers has positive and negative impacts; and 3) Social media influences the understanding of the religiosity of TNI AD Kodim 1403/Palopo soldiers at the level of understanding in the good category.